2017
DOI: 10.1007/s12020-017-1297-2
|View full text |Cite
|
Sign up to set email alerts
|

STEAP4 expression in human islets is associated with differences in body mass index, sex, HbA1c, and inflammation

Abstract: Six-transmembrane epithelial antigen of the prostate 4 (STEAP4) is a metalloreductase that has been shown previously to protect cells from inflammatory damage. Genetic variants in STEAP4 have been associated with numerous metabolic disorders related to obesity, including putative defects in the acute insulin response to glucose in type 2 diabetes (T2D). Purpose We examined whether obesity and/or T2D altered STEAP4 expression in human pancreatic islets. Methods Human islets were isolated from deceased donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In human islets, STEAP4 expression is reduced in obesity and hyperglycemia (HbA1c), but elevated in donors with high white blood cell count (Gordon et al 2017). Islet STEAP4 expression also appears to be slightly higher in women compared to men (Gordon et al 2017). To date, little is known about the function or localization of STEAP4 in islets and warrants further study.…”
Section: Steap4 Tissue and Cellular Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human islets, STEAP4 expression is reduced in obesity and hyperglycemia (HbA1c), but elevated in donors with high white blood cell count (Gordon et al 2017). Islet STEAP4 expression also appears to be slightly higher in women compared to men (Gordon et al 2017). To date, little is known about the function or localization of STEAP4 in islets and warrants further study.…”
Section: Steap4 Tissue and Cellular Expressionmentioning
confidence: 99%
“…Further, in human pancreatic islets, reduced STEAP4 gene expression correlates with increased BMI (Gordon et al 2017) among non-diabetic donors, but not among donors with T2D. Donors with T2Dshowed reduced STEAP4 gene expression with increased HbA1c, a key indicator of chronic hyperglycemia (Gordon et al 2017). On balance, these findings suggest that reduced STEAP4 expression is associated with obesity.…”
Section: Regulatory Influences On Steap4 Expressionmentioning
confidence: 99%
“…To investigate whether GLUT6 expression was also upregulated in obese and insulin-resistant human islets, we analyzed SLC2A6 mRNA levels in pancreatic islets from a cohort of human patients with and without type 2 diabetes with a body mass index (BMI) between 18 and 53. Donor information is as previously published [ 19 ] and given in Table S1 . These data showed that human islet SLC2A6 mRNA was significantly correlated with body mass index ( p = 0.005) ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…The source of the human islet samples from patients with or without type 2 diabetes used herein has been described previously [ 19 ]. Ethics approval was obtained from the University of Virginia Institutional Review Board (protocol #14904).…”
Section: Methodsmentioning
confidence: 99%
“…It was found to be highly expressed after the induction of TNF-α (6), and was later proven to be upregulated by other inflammatory cytokines such as IL-6 and IL-1β (7). A large number of studies have confirmed that STEAP4 is involved in the chronic inflammatory response of adipocytes during the pathogenesis of diabetes (7,8), and lower STEAP4 expression is associated with obesity and insulin resistance (9). Furthermore, some studies have shown that STEAP4 plays a protective role against inflammatory damage in hepatocytes (10), mesangial cells (11), and synovial cells (12).…”
Section: Introductionmentioning
confidence: 99%